Differentially expressed genes in PPARγ-deficient MSCs. (15th August 2018) - Su, Yun; Shen, Xiaona; Chen, Jie; Isales, Carlos M.; Zhao, Jing; Shi, Xing-Ming
Abstract: Peroxisome proliferator-activated receptor gamma (PPARγ) is a key regulator of adipogenesis. It is also a central player in energy metabolism, inflammation and immunity. As an important nuclear transcription factor, PPARγ can regulate the expression and function of genes or biological processes directly or indirectly via association with other factors and thus modulate their activities. To better understand the impact of PPARγ on the global gene expression profile, we evaluated the bioinformatic data, which revealed the changes that occurred in genes and their pathways in the absence of PPARγ. In brief, we performed RNA deep sequencing (RNA-Seq) analysis using RNA samples isolated from multipotent mesenchymal stromal cells (MSCs) of PPARγ knockout and wild type control mice. The RNA-Seq data sets were then subjected to bioinformatic analyses from various angles to better reveal the breadth of PPARγ function in different biological processes. Our results reveal novel genes and networks modulated by PPARγ and provides new insights into our understanding of the physiologic and pathophysiologic role this nuclear receptor plays in health and disease. Highlights: RNA-Seq analysis was performed to examine the expression profile of genes in PPARγ-deficient BMSCs. PPARγ plays roles in the development of the cardiovascular system, control of BP and in inflammation and immune functions. This study adds new information for NURSA by demonstrating a novel role of PPARγ on the expression of genes and pathways.